(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
This book is to be appreciated not only based on its content but also as a process entailing multi-scalar collaborations. In 2020, the Council for European Studies (CES), then homed at Columbia University, US, and the World Society Foundation (WSF), headquartered in Zurich, Switzerland, came together intending to sponsor a group of scholars from the “Global South” to attend the Annual Conference of Europeanists in Iceland. The goal of the partnership was to deliberately bring into European Studies scholars who often lack the opportunity to share their research at major international conferences because they reside outside Western Europe or North America. The program was built on the premise that the diversification of voices and the decentering of the production of knowledge about Europe could only enhance our understanding of Europe and the seeking of solutions to its problems. It was also expected that the scholars able to partake in the conference would have the opportunity to craft or strengthen their own networks with other Europeanists from all parts of Europe and the world. However, because of pandemic-related health risks and limitations on traveling, the conference, like many others around the world at the time, was postponed for an indeterminate duration. Rather than stalling the program, this impediment led us to reinvent the project and transform it into a year-long digital writing workshop, using Zoom to come together “in person.” Under the leadership of Nicole Shea, then Executive Director of CES, and Christian Suter, President of the WSF since 2008, this virtualization permitted even those scholars who would not have been able to come to the conference because of timing or distance—in spite of funding from WSF being granted—to fully participate, thereby expanding the anticipated geographical reach of the program.